PENGARUH SUHU PENCELUPAN TERHADAP KARAKTERISTIK MINUMAN TEH HERBAL KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) - Ardianta, I Komang; Yusa, Ni Made; Putra, I Nengah Kencana (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2019)
This research aimed to find out effect of the dipping water temperature on characteristics of  herbal tea drink from red dragon fruit peel. This study used the completely random design of treatment with dipping temperature treatment 50 o C, 60 o C, 70 o C, 80 o C, 90 o C and 100 o C . The treatment was repeated in 3 replications, resulting in 18 experimental units. Data were analyzed by variance analysis and continued with Duncan's test. The results showed that the dipping temperature of herbal tea drink from red dragon fruit peel affected the total phenol, antioxidant activity, color taste and overall appearance. The best treatment was obtained with temperature of 100 o C which produced herbal tea drinks with antioxidant activity (IC 50 ) which was 8.50 mg/ml, juice content 1.94%, total phenol 0.83 g/100g, and sensory characteristics of color was very red color and liked, ordinary aroma, taste liked and overall acceptance liked.